Pelaksanaan Skrining Anemia Pada Catin Wanita Di Puskesmas Tapin Utara Tahun 2021 - Norma, Norma; Zulliati, Zulliati; Yuliantie, Putri (Pusat Riset dan Inovasi Nasional, 2023)
Hb examination on female catin is useful to determine the status of anemia so that it can be prevented and intervened before pregnancy. According to the 2021 report of the Tapin District Health Office, the incidence of anemia in Catin was 160 people (14.1%) from 1135 catin examined. Puskesmas Tapin Utara is one of the puskesmas in Tapin regency that has provided reproductive health services to catin with the second most catin targets in Tapin district. The purpose of the study was to determine the implementation of anemia screening in women at the North Tapin health center. Quantitative descriptive observational research method on catin characteristics of anemic women through the reproductive health register instrument of the North Tapin Health Center in 2021. The results of the study of 130 women screened at the North Tapin health center in 2021 were 23 adolescents (17.7%), 107 adults (82.3). Very Thin category 12 people (9.2%), Thin category 23 people (17.7%), Normal 71 people (54.6%), Obese 10 people (7.7%), and Obesity 14 people (10.8%). Anemia 23 people (17.7%) and those who are not anemic 107 people (82.3%).